A sugarcane mosaic virus vector for gene expression in maize. (8th August 2019) - Mei, Yu; Liu, Guanjun; Zhang, Chunquan; Hill, John H.; Whitham, Steven A.
Abstract: Zea mays L. ssp. mays (maize) is an important crop plant as well as model system for genetics and plant biology. The ability to select among different virus‐based platforms for transient gene silencing or protein expression experiments is expected to facilitate studies of gene function in maize and complement experiments with stable transgenes. Here, we describe the development of a sugarcane mosaic virus (SCMV) vector for the purpose of protein expression in maize. An infectious SCMV cDNA clone was constructed, and heterologous genetic elements were placed between the protein 1 (P1) and helper component‐proteinase (HC‐Pro) cistrons in the SCMV genome. Recombinant SCMV clones engineered to express green fluorescent protein (GFP), β‐glucuronidase (GUS), or bialaphos resistance (BAR) protein were introduced into sweet corn (Golden × Bantam) plants. Documentation of developmental time courses spanning maize growth from seedling to tasseling showed that the SCMV genome tolerates insertion of foreign sequences of at least 1, 809 nucleotides at the P1/HC‐Pro junction. Analysis of insert stability showed that the integrity of GFP and BAR coding sequences was maintained longer than that of the much larger GUS coding sequence. The SCMV isolate from which the expression vector is derived is able to infect several important maize inbred lines, suggesting that this SCMV vector has potential to be a valuable tool for gene functional analysis in a broad range of experimentally important maize genotypes.